Transcutaneous Auricular Vagus Nerve Stimulation-Paired Rehabilitation for Oromotor Feeding Problems in Newborns: An Open-Label Pilot Study - Badran, Bashar W.; Jenkins, Dorothea D.; Cook, Daniel; Thompson, Sean; Dancy, Morgan; DeVries, William H.; Mappin, Georgia; Summers, Philipp; Bikson, Marom; George, Mark S. (Frontiers in Human Neuroscience, 2020)
Neonates born premature or who suffer brain injury at birth often have oral feeding disfunction and do not meet oral intake requirements needed for discharge. Low oral intake volumes result in extended stays in the hospital (>2 months) and can lead to surgical implant and explant of a gastrostomy tube (G-tube). Prior work suggests pairing vagus nerve stimulation (VNS) with motor activity accelerates functional improvements after stroke and transcutaneous auricular vagus nerve stimulation (taVNS) has emerged as promising noninvasive form of VNS. Pairing taVNS with bottle feeding rehabilitation may improve oromotor coordination and lead to improved oral intake volumes, ultimately avoiding the need for G-tube placement. We investigated whether transcutaneous auricular VNS (taVNS) paired with oromotor rehabilitation is tolerable, safe, and facilitates motor learning in infants who have failed oral feeding. We enrolled 14 infants (11 premature, 3 HIE) who were slated for gastrostomy tube (G-tube) placement, in a prospective, open-label study of taVNS-paired rehabilitation to increase feeding volumes. Once daily taVNS was delivered to the left tragus during bottle feeding for two weeks, with optional extension. The primary outcome was attainment of oral feeding volumes and weight gain adequate for discharge without G-tube while also monitoring discomfort and heart rate (HR) as safety outcomes. We observed no adverse events related to stimulation and stimulation-induced HR reductions were transient, safe and likely confirmed vagal engagement. Eight of 14 participants (57%) achieved adequate feeding volumes for discharge without G-tube (mean treatment length: 16±6 days). We observed significant increases in feeding volume trajectories in responders compared to pre-stimulation (p<0.05). taVNS-paired feeding rehabilitation appears safe and may improve oral feeding in infants with oromotor dyscoordination, increasing the rate of discharge without G-tube, warranting larger controlled trials.